Murine MPDZ‐linked hydrocephalus is caused by hyperpermeability of the choroid plexus. Issue 1 (5th December 2018) - Yang, Junning; Simonneau, Claire; Kilker, Robert; Oakley, Laura; Byrne, Matthew D; Nichtova, Zuzana; Stefanescu, Ioana; Pardeep‐Kumar, Fnu; Tripathi, Sushil; Londin, Eric; Saugier‐Veber, Pascale; Willard, Belinda; et al.
Abstract: Though congenital hydrocephalus is heritable, it has been linked only to eight genes, one of which is MPDZ . Humans and mice that carry a truncated version of MPDZ incur severe hydrocephalus resulting in acute morbidity and lethality. We show by magnetic resonance imaging that contrast medium penetrates into the brain ventricles of mice carrying a Mpdz loss‐of‐function mutation, whereas none is detected in the ventricles of normal mice, implying that the permeability of the choroid plexus epithelial cell monolayer is abnormally high. Comparative proteomic analysis of the cerebrospinal fluid of normal and hydrocephalic mice revealed up to a 53‐fold increase in protein concentration, suggesting that transcytosis through the choroid plexus epithelial cells of Mpdz KO mice is substantially higher than in normal mice. These conclusions are supported by ultrastructural evidence, and by immunohistochemistry and cytology data. Our results provide a straightforward and concise explanation for the pathophysiology of Mpdz ‐linked hydrocephalus. Synopsis: Dysfunction of the choroid plexus (CP) is a likely cause of hydrocephalus, but the underlying pathophysiological and molecular mechanisms remain unclear. Depletion of Mpdz, a cell junction protein, is shown here to induce paracellular and transcellular hyperpermeability of the CP in mice. Contrast medium leaks from the choroid plexus into the lateral ventricles of Mpdz −/− mice. Transmitted electron microscopy (TEM) of the CP of Mpdz −/− mice shows that intercellular junctions between the CP epithelial cells (CPECs) are structurally defective. The receptor to low‐density lipoprotein is overabundant in CPECs of Mpdz −/− mice by approximately 40%, and its constitutive transcytosis higher by more than 50% compared to CPECs of Mpdz +/+ mice. Fluid‐phase uptake is approximately two‐fold higher than Mpdz +/+ mice. Comparative proteomic analysis of the cerebrospinal fluid of Mpdz +/+ and Mpdz −/− mice finds protein overabundance in the latter, including more than 50‐fold abundance of ApoE. Abstract : Dysfunction of the choroid plexus (CP) is a likely cause of hydrocephalus, but the underlying pathophysiological and molecular mechanisms remain unclear. Depletion of Mpdz, a cell junction protein, is shown here to induce paracellular and transcellular hyperpermeability of the CP in mice.